(untitled) (Proceedings of the International Conference on Future of Women, 2020)
This study explores differences in South Korean newspaper coverage related to cases of sexual assault on females before and after the #MeToo movement. To this end, a content analysis was conducted to examine the framing of newspaper coverage of sexual assault by politicians in 2014 and 2018. In total, 755 news stories were analysed, revealing 10 times increase in the number of articles dealing with sexual violence cases after the #MeToo movement. In addition, it was found that the number of newspaper articles representing the voices of women who were victims of sexual assault or representing the position of women’s organizations calling for social change and the protection of women’s rights increased significantly after the #MeToo movement. In particular, a significant increase in newspaper coverage discussing problems with the legal system and calling for an urgent improvement to its dealings with sexual assault cases was found. Despite the #MeToo movement, however, the examined newspaper coverage still used an episodic frame more often than a thematic one in dealing with sexual violence against women and the articles still contained many provocative words, such as ‘adultery’ and ‘infidelity’, aimed at arousing readers’ curiosity and interest.